2013
DOI: 10.1007/s10964-013-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Neighborhood Collective Efficacy on Adolescent Substance Use and Violence Following Exposure to Violence

Abstract: Research has demonstrated that exposure to violence can result in many negative consequences for youth, but the degree to which neighborhood conditions may foster resiliency among victims is not well understood. This study tests the hypothesis that neighborhood collective efficacy attenuates the relationship between adolescent exposure to violence, substance use, and violence. Data were collected from 1,661–1,718 adolescents participating in the Project on Human Development in Chicago Neighborhoods (PHDCN), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
95
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 81 publications
9
95
0
Order By: Relevance
“…In fact, analyses did not include all possible contextual risk factors for substance use, such as physical or social disorder (e.g., Furr-Holden et al, 2011), tobacco and alcohol outlet density (e.g., Maimon and Browning, 2012; Tobler et al, 2009) and neighborhood levels of crime (e.g., Mrug and Windle, 2009). In addition, analyses did not examine the degree to which neighborhood factors moderated the impact of individual, peer and family influences on adolescent substance use, although other studies have shown such results (Fagan et al, 2014; Lo et al, 2006; Snedker et al, 2009; Wright et al, in press; Zimmerman and Vasquez, 2011). Likewise, we did not assess if neighborhood processes were mediated by influences in other contexts, as also demonstrated in past research (Chuang et al, 2005; Gibbons et al, 2004; Tobler et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, analyses did not include all possible contextual risk factors for substance use, such as physical or social disorder (e.g., Furr-Holden et al, 2011), tobacco and alcohol outlet density (e.g., Maimon and Browning, 2012; Tobler et al, 2009) and neighborhood levels of crime (e.g., Mrug and Windle, 2009). In addition, analyses did not examine the degree to which neighborhood factors moderated the impact of individual, peer and family influences on adolescent substance use, although other studies have shown such results (Fagan et al, 2014; Lo et al, 2006; Snedker et al, 2009; Wright et al, in press; Zimmerman and Vasquez, 2011). Likewise, we did not assess if neighborhood processes were mediated by influences in other contexts, as also demonstrated in past research (Chuang et al, 2005; Gibbons et al, 2004; Tobler et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Collective efficacy may also buffer the risk effect of neighborhood violence on mental health problems, such as substance use (Fagan, Wright, & Pinchevsky, 2014) and internalizing and externalizing problems (Browning et al, 2014). Beyond violence exposure, evidence for any protective effect of collective efficacy on other outcomes has rarely been studied in youth of any race.…”
mentioning
confidence: 99%
“…More recently, researchers have applied the concept of "collective efficacy" to explain neighborhood effect on crime and delinquency (Fagan and Wright 2012;Fagan, Wright, and Pinchevsky 2014;Morenoff et al 2001;Sampson 2006;Sampson et al 1997Sampson et al , 2005. Collective efficacy is "social cohesion among neighbors combined with their willingness to intervene on behalf of the common good" (Sampson et al 1997:918).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Collective efficacy is "social cohesion among neighbors combined with their willingness to intervene on behalf of the common good" (Sampson et al 1997:918). By analyzing the data from Human Development in Chicago Neighborhoods, several researchers have reported that the effects of social structural characteristics such as concentrated disadvantage and residential instability were mediated by collective efficacy (Sampson et al 1997), and that the effect of exposure to violence on substance abuse (Fagan et al 2014) or delinquency (Molnar et al 2008) was moderated by neighborhood collective efficacy. Also, it was reported that community characteristics such as "local organizations," "voluntary associations," and "friend/kinship networks" played important roles in inhibiting delinquency as long as they facilitated the collective efficacy of residents in achieving social control (Morenoff et al 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%